Anhydrous Alum Inhibits α-MSH-Induced Melanogenesis by Down-Regulating MITF via Dual Modulation of CREB and ERK - In, Kyu Ree; Kang, Mi Ae; Kim, Su Dong; Shin, Jinho; Kang, Sung Un; Park, Tae Jun; Kim, Seung Joo; Lee, Jong Soo (International Journal of Molecular Sciences, 2023)
Melanogenesis, the intricate process of melanin synthesis, is central to skin pigmentation and photoprotection and is regulated by various signaling pathways and transcription factors. To develop potential skin-whitening agents, we used B16F1 melanoma cells to investigate the inhibitory effects of anhydrous alum on melanogenesis and its underlying molecular mechanisms. Anhydrous alum (KAl(SO4)2) with high purity (>99%), which is generated through the heat-treatment of hydrated alum (KAl(SO4)2·12H2O) at 400 °C, potentiates a significant reduction in melanin content without cytotoxicity. Anhydrous alum downregulates the master regulator of melanogenesis, microphthalmia-associated transcription factor (MITF), which targets key genes involved in melanogenesis, thereby inhibiting α-melanocyte-stimulating hormone (α-MSH)-induced melanogenesis. Phosphorylation of the cAMP response element-binding protein, which acts as a co-activator of MITF gene expression, is attenuated by anhydrous alum, resulting in compromised MITF transcription. Notably, anhydrous alum promoted extracellular signal-regulated kinase phosphorylation, leading to the impaired nuclear localization of MITF. Overall, these results demonstrated the generation and mode of action of anhydrous alum in B16F1 cells, which constitutes a promising option for cosmetic or therapeutic use.
Keywords: alpha-MSH; Cell Line, Tumor; Melanins; Microphthalmia-Associated Transcription Factor; Monophenol Monooxygenase; anhydrous alum; CREB; ERK; melanogenesis; MITF